‘It Is Said That at Least 300,000 rt of Capital are Required for a Raft Trade’ : German Traders and the Dutch Timber Trade in the Eighteenth Century - Banken, Ralf (TSEG - The Low Countries Journal of Social and Economic History, 2024)
Although the Dutch timber trade from the seventeenth to the nineteenth century has been the subject of many historical studies, the development of the capital-intensive timber wholesale trade has remained rather underexposed by economic historians with regard to the actors involved. This is surprising since a capital of up to 600,000 Reichstaler had to be raised for the Dutch timber trade; amounts that were hardly invested in any other commercial enterprise in Germany at the time. The article therefore focuses on the timber wholesalers of the eighteenth century and analyzes in detail, based on our own archival research and previous research results, how the timber wholesalers organized their business (business strategies, business practices, etc.) and what significance their income had for the economic development of the participating economic regions of West and South-West Germany in the long term. It appears that around 1750 the German timber wholesaler and the timber companies from the Black Forest had long since driven out their Dutch competitors and acquired large fortunes. With the Dutch timber trade, capitalist practices (creation and management of companies, accounting, new methods of credit financing, etc.) also spread, which also formed an important building block for the further development of the South-West and West German economy. However, the most important thing was undoubtedly the emergence of a risk-loving entrepreneurial class with a sufficient capital base and business knowledge, which had long since broken away from 'artisan' self-reliance. Because the timber wholesalers often also invested their capital acquired in the Dutch timber trade in other industries, and these often formed a crystallization point for the West and South-West German industrialization after 1815, it can be said that the timber trade with the Netherlands not only generated an enormous volume in the eighteenth century and supported West German economic growth from 1740 onwards, but in the long term also contributed to the economic and social structural changes of the nineteenth century.